HUBUNGAN ANTARA JARAK KEHAMILAN UMUR DAN PARITAS DENGAN LAMA PERSALINAN KALA I DI KAMAR BERSALIN RSU ANUTAPURA PALU - mutmaina mutmaina (Journal of Hospital Administration and Management (JHAM), 2022)
Background: Prolonged labor during the first stage of childbirth remains one of the leading causes of maternal and neonatal morbidity. Maternal characteristics, including pregnancy interval, maternal age, and parity, are recognized as important factors influencing the progress and duration of labor. Early identification of these risk factors is essential to improve maternal healthcare services and reduce obstetric complications. Objective: This study aimed to determine the relationship between pregnancy interval, maternal age, and parity with the duration of the first stage of labor among women delivering at the Delivery Room of Anutapura General Hospital, Palu. Methods: This study employed a quantitative analytical design with a cross-sectional approach. The research was conducted from May to June 2020 and involved 33 mothers who delivered at the Delivery Room of Anutapura General Hospital, Palu. Data were analyzed using the Chi-square test with a significance level of 0.05. Odds Ratios (ORs) were calculated to estimate the strength of the associations between maternal characteristics and prolonged first-stage labor. Results: The findings revealed significant associations between pregnancy interval and the duration of the first stage of labor (p = 0.005; OR = 20.0), maternal age and the duration of the first stage of labor (p = 0.004; OR = 33.3), and parity and the duration of the first stage of labor (p = 0.009; OR = 13.7). Mothers with an inadequate pregnancy interval, those aged below 20 years, and primigravida mothers were more likely to experience prolonged first-stage labor than their respective counterparts. Conclusion: Pregnancy interval, maternal age, and parity were significantly associated with the duration of the first stage of labor. Early identification of these maternal risk factors during antenatal care is recommended to support timely interventions, improve labor management, and reduce maternal and neonatal complications.